A case of radiation-associated angiosarcoma after breast cancer - Nanae Horisawa; Yayoi Adachi; Masataka Sawaki; Masaya Hattori; Akiyo Yoshimura; Naomi Gondo; Haruru Kotani; Ayumi Kataoka; Kayoko Sugino; Makiko Mori; Mitsuo Terada; Yuri Ozaki; et al. (Surgical Case Reports, 2018)
Abstract Background Radiation-associated angiosarcoma (RAAS) is a rare subtype of secondary angiosarcoma that is characterized by rapid proliferation and extensive tissue infiltration. Although various treatments for RAAS (such as surgery, chemotherapy, and radiation therapy) have been reported, there is no consensus as to which approach is the best. Case presentation A 76-year-old woman presented with right breast cancer (T1N0M0, stage I) 9 years ago. She had undergone breast-conserving surgery and sentinel lymph node biopsy and was receiving adjuvant chemotherapy and radiation therapy for the malignancy. Six years after presenting with the tumor, she developed pigmented skin and was diagnosed with a RAAS; this angiosarcoma recurred three times within 2 years. The angiosarcoma was resected each of the three times, after which adjuvant radiation therapy was performed. At 76 years old, the patient developed a new mass on her chest skin in the vicinity of the scar. Angiosarcoma was diagnosed following a pathology report, which resulted in a second diagnosis of recurrent RAAS again since the diagnostic criteria were met. After extensive resection of the irradiated area, the patient has remained free of angiosarcoma for the last 3 years. Conclusion Resection of the entire irradiated field is critical for successful treatment of RAAS.